1996
DOI: 10.1006/anbe.1996.0032
|View full text |Cite
|
Sign up to set email alerts
|

Social organization in the aboriginal house mouse,Mus spretus Lataste: behavioural mechanisms underlying the spatial dispersion of competitors

Abstract: Abstract. Because rodents behave cryptically and often have large home ranges, the role of social defence in determining their spatial dispersion in grassland remains an enigma. Individual dispersion and access to resources could be determined mainly by the aggressive exclusion of intruders from large territories by residents, or by the scattered distribution of resources and avoidance of dominant competitors occupying preferred sites. The ways in which predictions from these two hypotheses correspond to intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 26 publications
5
42
1
Order By: Relevance
“…The low levels of agonistic behavior in both females and males of M. spretus seem rather surprising, yet it fits very well with the finding of Hurst et al [1996] that dominance over suitable sites is more important than investment in fierce aggression to drive competitors away in this free-ranging species. In other words, while fighting for scattered food is profitable and yields essential gains, it is probably wiser to find one's own shelter than to risk injuries associated with driving other mice out from already occupied shelters.…”
Section: Discussionsupporting
confidence: 71%
“…The low levels of agonistic behavior in both females and males of M. spretus seem rather surprising, yet it fits very well with the finding of Hurst et al [1996] that dominance over suitable sites is more important than investment in fierce aggression to drive competitors away in this free-ranging species. In other words, while fighting for scattered food is profitable and yields essential gains, it is probably wiser to find one's own shelter than to risk injuries associated with driving other mice out from already occupied shelters.…”
Section: Discussionsupporting
confidence: 71%
“…Even territorial species of salamanders out of the breeding period may be attracted to conspecific chemical cues when the other choice is a substrate with no odour (Verrell and Davis 2003). Previous studies with vertebrates showing conspecific attraction have suggested that individuals might assess site quality through conspecific chemical cues (Hurst et al 1996;Luque-Larena et al 2001;Aragón et al 2006b). Fig.…”
Section: Discussionmentioning
confidence: 97%
“…The sedentary nature of older males, at the start of reproduction, suggests territorial organization (Cassaing 1984;Cassaing and Croset 1985). Nevertheless, tests performed on captive animals show that Mus spretus does not fiercely attempt to exclude others from its territory, but suggest that mice establish a dominance relationship using stylized submission postures and are relatively tolerant (Hurst et al 1996). This behavior is quite different from that of resident M. musculus, which are highly intolerant and aggressive toward unfamiliar intruders, which readily take flight to avoid resident attacks .…”
Section: Behaviormentioning
confidence: 98%